(untitled) (Spectrum Journal of Innovation, Reforms and Development, 2024)
Digital transformation in Central Asia is driving economic change with significant growth in e-commerce, digital infrastructure investment and the emergence of technology-based industries. These developments are fostering regional industrial cooperation by increasing connectivity, efficiency and innovation across borders. The article analyzes the importance of several factors in promoting digital innovations and creating a favorable environment for the flourishing of the digital economy and integration into industrial cooperation.